Heartfelt empathy? No association between interoceptive awareness, questionnaire measures of empathy, reading the mind in the eyes task or the director task - Ainley, Vivien; Maister, Lara; Tsakiris, Manos (Frontiers in Psychology, 2015)
Interoception, defined as afferent information arising from within the body, is the basis of all emotional experience and underpins the ‘self’. However, people vary in the extent to which interoceptive signals reach awareness. This trait modulates both their experience of emotion and their ability to distinguish ‘self’ from ‘other’ in multisensory contexts. The experience of emotion and the degree of self/other distinction or overlap are similarly fundamental to empathy, which is an umbrella term comprising affect sharing, empathic concern and perspective-taking. A link has therefore often been assumed between interoceptive awareness and empathy despite a lack of clear evidence. To test the hypothesis that individual differences in both traits should correlate, we measured interoceptive awareness in four experiments, using a well-validated heartbeat perception task, and compared this with scores on several tests that relate to various aspects of empathy. We firstly measured scores on the Index of Interpersonal Reactivity and secondly on the Questionnaire of Cognitive and Affective Empathy. Thirdly, because the ‘simulationist’ account assumes that affect sharing is involved in recognising emotion, we employed the ‘Reading the Mind in the Eyes Task’ for the recognition of facial expressions. Contrary to expectation, we found no significant relationships between interoceptive awareness and any aspect of these measures. This striking lack of direct links has important consequences for hypotheses about the extent to which empathy is necessarily embodied. Finally, to assess cognitive perspective-taking ability, which specifically requires self/other distinction, we used the ‘Director Task’ but found no relationship. We conclude that the abilities that make up empathy are potentially related to interoceptive awareness in a variety of conflicting ways, such that a direct association between interoceptive awareness and various components of empathy has yet to be established.